2016
DOI: 10.1111/cas.12952
|View full text |Cite
|
Sign up to set email alerts
|

miR‐199a‐5p regulates β1 integrin through Ets‐1 to suppress invasion in breast cancer

Abstract: Increasing evidence has revealed that miR‐199a‐5p is actively involved in tumor invasion and metastasis as well as in the decline of breast cancer tissues. In this research, overexpression of miR‐199a‐5p weakened motility and invasion of breast cancer cells MCF‐7 and MDA‐MB‐231. Upregulation of Ets‐1 increased breast cancer cell invasion, but the mechanism by which miR‐199a‐5p modulates activation of Ets‐1 in breast cancer was not clarified. We investigated the relationship between miR‐199a‐5p and Ets‐1 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Consistent with these results, the levels of miR‐199 family members are downregulated in metastatic lesions in contrast with the primary tumor as seen in clinical samples of colon cancers, and miR‐199 suppresses colon cancer metastasis in vivo . It has been suggested that the miR‐199 family regulates the progression and metastasis of various cancers other than colon cancer, including liver, ovarian, prostate, and breast cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results, the levels of miR‐199 family members are downregulated in metastatic lesions in contrast with the primary tumor as seen in clinical samples of colon cancers, and miR‐199 suppresses colon cancer metastasis in vivo . It has been suggested that the miR‐199 family regulates the progression and metastasis of various cancers other than colon cancer, including liver, ovarian, prostate, and breast cancers .…”
Section: Discussionmentioning
confidence: 99%
“…44 Villari et al group was able to identify interaction between fascin and FAK that in turn controls focal adhesion stability and motility. 48 Elevated expression of fascin and ITGB1 were independently reported in various cancers including breast and were found to associate with enhanced self-renewability, which present serious challenge to effective treatment of cancer. It is possible to speculate that fascin influences β1 integrin expression and its downstream-related function via targeting selected miRNAs, which have gained much attention in recent years due to their functions in RNA silencing and post-transcriptional regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that miRNAs function via regulating their target protein by binding to the 3’ untranslated regions (UTRs) of target messenger RNAs (mRNAs), resulting in mRNA degradation or the blockade of mRNA translation . Previously, miR‐199a‐5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia‐inducible factor 1 alpha (HIF‐1α), E‐cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin‐dependent kinase inhibitor 1C (P57, CDKN1C) …”
Section: Discussionmentioning
confidence: 99%
“…In present study, we showed that miR-199a-5p, frequently down- 19,20 Previously, miR-199a-5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia-inducible factor 1 alpha (HIF-1α), E-cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin-dependent kinase inhibitor 1C (P57, CDKN1C). [21][22][23][24][25][26][27][28][29] Clathrin is considered the prototype vesicle coat protein whose self-assembly mediates sorting of membrane cargo and recruitment of lipid modifiers. 30 In the past decades, most of studies were focused on clathrin mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%